1994
DOI: 10.1021/jm00047a004
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Properties of Polyamine Analogs: A Structure-Activity Study

Abstract: A basis set of polyamine analogues was designed and synthesized. These compounds were used to initiate a systematic investigation of the role of chain length, terminal nitrogen alkyl group size, and symmetry of the methylene backbone in the antineoplastic properties of polyamine analogues. New synthetic methods predicated on our earlier polyamine fragment synthesis are described for accessing the tetraamines of interest. An unsymmetrically substituted diamine reagent, N-(tert-butoxycarbonyl)-N,N'-bis(mesitylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
194
1
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(200 citation statements)
references
References 10 publications
4
194
1
1
Order By: Relevance
“…Furthermore, drug treatment for 48 h and 96 h did not lead to markedly enhanced cell growth inhibition. These observations are also in contrast to data for the in vitro growth inhibitory properties of several polyamine analogues against other cancer cell types, which showed that IC 50 values decrease considerably as drug exposure time increases from 48 to 96 h [33]. Although the intracellular metabolism of sulphonamido oxa-polyamines is not yet known, the possibility that they are transformed into less toxic compounds could be further explored by finding an explanation for the lack of correlation between the cytotoxicity and the duration of incubation.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, drug treatment for 48 h and 96 h did not lead to markedly enhanced cell growth inhibition. These observations are also in contrast to data for the in vitro growth inhibitory properties of several polyamine analogues against other cancer cell types, which showed that IC 50 values decrease considerably as drug exposure time increases from 48 to 96 h [33]. Although the intracellular metabolism of sulphonamido oxa-polyamines is not yet known, the possibility that they are transformed into less toxic compounds could be further explored by finding an explanation for the lack of correlation between the cytotoxicity and the duration of incubation.…”
Section: Discussioncontrasting
confidence: 99%
“…Although inhibitors of virtually all of the biosynthetic enzymes in polyamine metabolism have been synthesized, none has demonstrated clinical efficacy as a single agent in clinical trails for cancer (see [20]). In an attempt to overcome the limitations encountered with specific inhibitors of enzyme function, we and others have exploited the self-regulatory properties of polyamine metabolism for therapeutic advantage through the use of structural analogues of the natural polyamines [4,5,8,18,39,43,44,49]. The initial studies with polyamine analogues, particularly with BENSpm, were promising, but clinical trials with a number of analogues in lung, breast, and other tumors did not reveal efficacy as single agents.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the key enzymes involved in the polyamine biosynthetic pathway, ornithine decarboxylase (ODC) and S-adenosylmethionine decarboxylase (AdoMetDC) has been demonstrated to be successful as a means of targeting polyamines and regulating cell growth, but has had limited clinical success [2,33,38]. In an attempt to overcome the shortcomings of the inhibitors of polyamine biosynthesis, several groups have synthesized and tested polyamine analogues that were designed to take advantage of the self-regulatory properties of the natural polyamines [4,18,26,55].…”
Section: Introductionmentioning
confidence: 99%
“…Association of polyamines with nucleic acids and protein is included in their mechanism of action. The aim of this study was to examine the interaction of human serum albumin (HSA) with several polyamine analogues such as 1,3,7,11,7,11,15, in aqueous solution at physiological conditions, using a constant protein concentration and various polyamine contents (μM to mM). FTIR, UVvisible and CD spectroscopic methods were used to determine the polyamine binding mode and the effects of polyamine complexation on protein stability and secondary structure.…”
Section: Introductionmentioning
confidence: 99%